PENGARUH BAURAN PEMASARAN DAN LOYALITAS MEREK TERHADAP KEPUASAN NASABAH MENABUNG PADA TABUNGAN SIKOCI BANK NAGARI CABNAG PEKANBARU - Sari, Ireni Adila; Heriyanto, Meyzi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The purpose of this study was to determine the effect of the marketing mix and brand loyalty toward customer satisfaction save savings sikoci Bank Nagari Pekanbaru Branch. This research method is quantitatively using SPSS 21 program, where samples were used that sikoci savings customers who use savings products sikoci by respondents as many as 100 people. The sampling technique used was accidental sampling slovin formula. This study has shown that the results of hypothesis testing t test, t known t arithmetic (5966)> t table (1.985) and sig. (0000)> 0.05. means the marketing mix variables significantly influence customer satisfaction. t (7011)> t table (1.985) and sig (0000) <0:05 means brand loyalty variables significantly influence customer satisfaction.Key words : marketing mix, brand loyalty, customer satisfaction